Space Maintainer: A Review - Subhashree Samal (Indian Journal of Forensic Medicine & Toxicology, 2020)
Space maintainers are useful incases of deciduous teeth to protect the dentition from malposition,impaction,crowding,etc. They can also be used inmixeddentition. Various types of space maintainersare there forParticular treatment. This is mainly aimed atthe management of space in children. This article mainly aimsat Bandandloop,Distal shoe, and trans palatal arch space maintainers.